Vulgar Terms in Communication Among Mobile Legends Players: A Pragmatic Analysis - Aditiawarman, Mac; Maharani, Dara (Jurnal Ilmiah Langue and Parole, 2024)
This research discusses swear word and forms of use of vulgar terms between players in Mobile Legends. The discussion of this research focuses on the use of swearing in Mobile Legends player communication. The use of swear words and vulgar terms is often found among the public, such as on social media and especially in games such as the Mobile Legends game, In the Mobile Legends game there are often find the use of bad words, such as insults or other vulgar words, this happens when there are several players who play a game that is not good, resulting in defeat which can be detrimental to the entire team, including the other players, the player will lose their score or level that previously obtained. This research is a study of pragmatic elements that uses theory from Ljung (2011), which discusses tip types and their functions. This research aims to identify forms of use of swear words in the communication of Mobile Legends players. This research was carried out using qualitative methods. The data analysis method in this research was carried out by classifying data taken from conversations between Mobile Legends players. The results of the research show that there are 5 data from the circumstance swearing, 4 which state the use of the term sex organ swearing, 3 the use of sexual activities swearing, 2 the term family swearing, 3 from swearing animals swearing and 1 the use of religious swearing and 1 from the use of prostitution swearing.